K63-linked ubiquitylation induces global sequestration of mitochondria - Richard, Thibaud J. C. (Sci Rep, 2020)
Even though K63-linked polyubiquitin chains do not target proteins for proteasomal degradation, they play nevertheless a complementary protective role in maintaining protein homeostasis by directing malfunctioning proteins and organelles to inclusion bodies or autophagosomes. A paradigm for this process is the sequestration and autophagic degradation of dysfunctional mitochondria. Although studies have shown that K63-ubiquitylation of mitochondrial proteins by the ubiquitin ligase Parkin is important in this process, it is presently not clear if this modification also suffices to initiate this cascade of events. To address this question, we have engineered the ubiquitin ligase ProxE3, which in an inducible manner synthesizes K63-linked ubiquitin chains on the surface of mitochondria. We found that the presence of K63-linked ubiquitin chains on mitochondria resulted in the recruitment of the ubiquitin adaptor p62 and induced a dramatic redistribution of mitochondria, which was reminiscent to the Parkin-facilitated sequestration in response to mitochondrial uncoupler. However, ProxE3 did not induce autophagic degradation of mitochondria. Our data show that K63-linked ubiquitin chains at the mitochondrial membrane are sufficient for the induction of mitochondrial sequestration, but not mitophagy, without the need of extrinsically inflicting mitochondrial dysfunction.